Cellular apoptosis susceptibility (CSE1L/CAS) protein in cancer metastasis and chemotherapeutic drug-induced apoptosis - Tai Cheng-Jeng; Hsu Chung-Huei; Shen Shing-Chuan; Lee Woan-Ruoh; Jiang Ming-Chung (Journal of Experimental & Clinical Cancer Research, 2010)
Abstract The cellular apoptosis susceptibility (CSE1L/CAS) protein is highly expressed in cancer, and its expression is positively correlated with high cancer stage, high cancer grade, and worse outcomes of patients. CSE1L (or CAS) regulates chemotherapeutic drug-induced cancer cell apoptosis and may play important roles in mediating the cytotoxicities of chemotherapeutic drugs against cancer cells in cancer chemotherapy. CSE1L was originally regarded as a proliferation-associated protein and was thought to regulate the proliferation of cancer cells in cancer progression. However, the results of experimental studies showed that enhanced CSE1L expression is unable to increase proliferation of cancer cells and CSE1L regulates invasion and metastasis but not proliferation of cancer cells. Recent studies revealed that CSE1L is a secretory protein, and there is a higher prevalence of secretory CSE1L in the sera of patients with metastatic cancer. Therefore, CSE1L may be a useful serological marker for screening, diagnosis and prognosis, assessment of therapeutic responses, and monitoring for recurrence of cancer. In this paper, we review the expression of CSE1L in cancer and discuss why CSE1L regulates the invasion and metastasis rather than the proliferation of cancer.